PENENTUAN RUTE TERDEKAT LOKASI KLINIK BERSALIN DI KOTA SURAKARTA MENGGUNAKAN ALGORITMA FLOYD WARSHALL - Taratya Indra Pratiwi; Yustina Retno Wahyu Utami; Sri Hariyati Fitriasih (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2018)
Maternity clinics are an option for mothers who will give birth, in addition to locations that are more affordable than hospitals, the place is evenly spread so that their presence can be identified. Maternity Clinic was also chosen because some mothers feel anxious to give birth in a hospital environment, conditions that can slow contractions, make labor longer and interventions are more likely. So giving birth to a baby in a maternity clinic is an alternative that is widely chosen. But not all of them know the location of the nearest Maternity Clinic. Then you will find a way to help find the location of the Maternity Clinic in the city of Surakarta to be faster. The purpose of this study was to make it easier to find where the maternity clinic was located and be able to facilitate and provide access to the community who needed a search for a maternity clinic in the Surakarta area. This research proposes Floyd Warshall algorithm to provide the shortest route. The data used is clinic location data obtained from the Health Office. The results of this research are the shortest route that is connected in the Google Map, namely information on the location of Maternity Clinic locations and nodes scattered in the Surakarta area which can be of benefit to the community about Maternity Clinic places.Keywords: Floyd Warshall Algorithm, Geographic Information System, Maternity Clinic, The Shortest Route